Understanding the Charter of Workers’ Rights in its historical context - Pasquino, Gianfranco (PSL Quarterly Review, 2021)
The Charter of Workers’ Rights was a major achievement of the Italian Socialist Party and of the center-left governments. This article explores some of the factors in the international context that allowed for a period of reforms in Italy. Changes in the policies of the US administration; a difficult leadership succession in the Communist Party of the Soviet Union; the renewal of the Catholic Church thanks to the Vatican Council; and the enlargement of the Italian working class plus the role of the Socialist Minister of Labor must all be given credit for a truly significant piece of legislation. The Charter also contained a vision of the future, of a new society, still to come. JEL codes: J5, K31, Z13